2014
DOI: 10.4238/2014.january.22.4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of TP53 gene expression and p53 level of human hypopharyngeal FaDu (HTB-43) head and neck cancer cell line after microRNA-181a inhibition

Abstract: ABSTRACT. The identification of new biomarkers for early detection of highly recurrent head and neck cancer is urgently needed. MicroRNAs (miRNAs) are small and non-coding RNAs that regulate cancer-related gene expression, such as tumor protein 53 (TP53) gene expression. This study was carried out to analyze TP53 gene expression using real-time PCR and to determine changes in intracellular p53 level by flow cytometry after downregulation of miRNA-181a miRNA inhibitor in the FaDu cell line. TP53 gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
1
1
Order By: Relevance
“…As the samples in the current study were collected from the archive with limited number and type of nasopharynx samples, some inevitable differences existed between the current and previous study, which were clinical material (formalin instead of RNAlater fixation) and type of tissues used for non-NPC control group (normal, lymphoma and inflammation instead of normal only). Even though the clinical material used in the current study was slightly different with the previous study, several studies showed that miRNA expression in FFPE samples was highly correlated to miRNA expression in fresh frozen samples, which is comparable to RNAlater fixed samples [28][29][30]. Another study by Vojtechova et al [33] could not find a better correlation values of miRNA expression profiles in fresh frozen with FFPE samples.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…As the samples in the current study were collected from the archive with limited number and type of nasopharynx samples, some inevitable differences existed between the current and previous study, which were clinical material (formalin instead of RNAlater fixation) and type of tissues used for non-NPC control group (normal, lymphoma and inflammation instead of normal only). Even though the clinical material used in the current study was slightly different with the previous study, several studies showed that miRNA expression in FFPE samples was highly correlated to miRNA expression in fresh frozen samples, which is comparable to RNAlater fixed samples [28][29][30]. Another study by Vojtechova et al [33] could not find a better correlation values of miRNA expression profiles in fresh frozen with FFPE samples.…”
Section: Discussioncontrasting
confidence: 56%
“…In Malaysia, so far, there was one published study by Nurul-Syakima et al [25] that profiled the miRNA expression in head and neck cancers using human biopsies, in which NPC biopsies were included. However, detailed analyses in that study was only limited to investigate the roles of miRNAs in HSCC, excluding the NPC [28,29]. In this study, we took the initiative to determine the expression of miR-101 and miR-744, the miRNAs that were found to be miR-101 and miR-744 in Nasopharyngeal Carcinoma Azmir AHMAD et al http://wjst.wu.ac.th differentially expressed in the study by Nurul-Syakima et al [25], in NPC biopsies and analyse statistically on their performance to be biomarkers for NPC.…”
Section: Discussionmentioning
confidence: 99%